2020
DOI: 10.15625/0866-7187/42/3/15454
|View full text |Cite
|
Sign up to set email alerts
|

Application of GIS-Base GALDIT for vulnerability assessment to saltwater intrusion of Holocene coastal aquifer: a case of Quang Nam - Da Nang city, Vietnam

Abstract: Groundwater is an essential resource which is influenced by salt water due to the groundwater exploitation in Holocene aquifer of Quang Nam - Da Nang. Hence, the measures for preventing saltwater intrusion and better groundwater management are required. In this study, GALDIT method was utilized to identify the salt water intrusion (SWI) vulnerability zones using monitoring data in Holocene aquifer of Quang Nam - Da Nang. The results of GALDIT method indicated that Da Nang and Hoi An cities were in the high SWI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Saltwater origin and mechanisms in coastal aquifers in Vietnam have been studied extensively and the main causes identified are groundwater exploitation [9]; inter-aquifer leakage due to diffusion and density flow or high hydraulic gradient [10].…”
Section: Introductionmentioning
confidence: 99%
“…Saltwater origin and mechanisms in coastal aquifers in Vietnam have been studied extensively and the main causes identified are groundwater exploitation [9]; inter-aquifer leakage due to diffusion and density flow or high hydraulic gradient [10].…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam, in recent years, many researchers have become interested in using the GALDIT model to assess the vulnerability of coastal aquifers to saline intrusion [18][19][20][21]. However, the majority of research still applies the original weights of the method framework and has not shown the spatial distribution visualization of each component parameter.…”
Section: Introductionmentioning
confidence: 99%
“…According to the parameters, "the height of groundwater level", "the distance from the study site to the saline line", and "the impact of existing status of seawater intrusion", the very high vulnerability zones were close to the saline boundary and had a large water-lowering funnel. Similarly, Phan Nam Long and Huynh Tien Dat [19] also applied GALDIT based on GIS to assess groundwater vulnerability due to seawater intrusion in Quang Nam and Da Nang. They identified areas of high vulnerability distributed along the coast and in densely populated areas near rivers.…”
Section: Introductionmentioning
confidence: 99%